2018
DOI: 10.1200/po.17.00211
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Gene Alterations in an Asian Population With Triple-Negative Breast Cancer

Abstract: Purpose It has been suggested that the biologic characteristics of breast cancer may differ among different geographic or ethnic populations. Indeed, triple-negative breast cancer (TNBC), the most lethal breast cancer subgroup, has been reported to occur at a higher incidence in Japan than in the United States. However, most genomic studies of these tumors are from Western countries, and the genomic landscape of TNBC in an Asian population has not been thoroughly investigated. Here, we sought to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Our data are consistent with previous evidence, i.e. that mutation of TP53 ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Nagahashi et al, 2018 ) and amplification of MYC ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Curtis et al, 2012 ) are the two most common genetic aberrations in TNBC, and frequently occur in combination ( Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are consistent with previous evidence, i.e. that mutation of TP53 ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Nagahashi et al, 2018 ) and amplification of MYC ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Curtis et al, 2012 ) are the two most common genetic aberrations in TNBC, and frequently occur in combination ( Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Developing genetic models for TNBC is challenging. Most TNBCs contain mutations in TP53 , but some other genes are also commonly mutated ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Nagahashi et al, 2018 ). However, computational work ( Cancer Genome Atlas Network, 2012 ; Jiang et al, 2019 ; Mermel et al, 2011 ; Sanchez-Garcia et al, 2014 ; Curtis et al, 2012 ) has identified extensive genomic copy number alterations (CNAs) that define regions that commonly overlap between different patients.…”
Section: Introductionmentioning
confidence: 99%
“…Racial and ethnic population‐specific cancer driver alterations and single nucleotide polymorphisms (SNPs) may complicate the evaluation and interpretation of the results of genetic analyses. Several studies have reported obvious racial differences in cancer‐specific driver alterations among Japanese individuals . Furthermore, 15% of SNPs are reportedly specific to Japanese individuals, thus affecting the evaluation of the clinical significance of genetic alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large single-cell RNA Sequencing analysis study on chemotherapy-treated patients by Kim et al (2018) demonstrates that resistance to chemotherapy is mainly adaptive in nature and NACT nongenetically selects residual tumor cells due to transcriptional and molecular reprogramming (Kim et al 2018). Few genomic studies on Asian TNBC cohorts from Japan and China detect actionable genetic vulnerabilities like alteration in MYC and PTK2 (Kovacevic et al 2016)(DOI: 10.1200/po.17.00211), while the top altered genes in recurrence in Chinese patients were TP53, PTEN, RB1, PIK3CA and BRCA1 (Nagahashi et al 2018(Nagahashi et al )(10.1080(Nagahashi et al /07853890.2021. These studies indicate that Asian TNBC tumors also exhibit genomic makeups not much different from the Western population, as reported in TCGA TNBC data.…”
mentioning
confidence: 99%